Validation of Two Extraction Methods for Human DNA from Cigarette Butts - Sales, Paul Ryan L.; Ferrer, Dorothy Emma C.; Calacal, Gayvelline C.; Salvador, Jazelyn M.; De Ungria, Maria Corazon A. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 31 No 1 (2019), 2019)
Cigarette butts found in crime scenes may be used to identify persons and link them to a crime through DNA prof iling of epithelial cells from saliva stains on these materials. Downstream analysis of cigarette butts poses some challenges because these are often exposed to chemical contaminants and environmental conditions which lead to DNA degradation. In this study, several factors were tested to compare the amount and quality of DNA obtained from cigarette butts extracted using an organic procedure and the QIAamp® DNA Micro Kit (QIAGEN). Results show that exposure to an outside environment had a significant effect on DNA yield and amplifiability for both extraction procedures. Prolonged storage of cigarette butts of up to six months affected the amount of DNA that can be extracted using the QIAamp® DNA Micro Kit. However, complete DNA profiles can be generated from cigarette butts stored for six months provided that these samples are stored indoors under controlled temperature conditions and with minimal exposure to contaminants. Keywords: Cigarette butts, DNA typing, DNA yield, forensic science